HUBUNGAN ANTARA PENGGUNAAN BAK MANDI DENGAN RISIKO TERJADINYA PENYAKIT DEMAM BERDARAH DENGUE DI WINONG KOTAGEDE YOGYAKARTA TAHUN 2015 - Amyati Amyati (STIKes Surya Global Yogyakarta, 2017)
Background: Bath Tub is one of breading places of DBD (Dengue Fever) Vector. Presence or absence of Aedes mosquito larvae in a bath tub is depend on the type, color, material,condition and volume of bath tub.Purpose: the purpose of this study was to know the relationship of bath tub volume with presence of Aedes Aegypti Morsquito larvae and relationship between bath tub volume with dengue fever case in Winong Kotagede Yogyakarta.Methods: the method of this study was observational analysis with statistical chi square. Data collecting was done by using larvae survey of bath tub in the house and also larvae single method. The result of statistic tes used pearson chi square.Result: there was a different significant between the biggest, big, middle bath tub of larvae (H1= 74, 28 %, C1= 76,79 %) There was a significant between bath tub volume with larvae. There was a relationship between bath tub volume with dengue fever by using pearson chi square.it showed that the value of 16, 308 and sig P=0,001. Spearmen correlation showed value of 0,515 and sig p=0,000. The value of sig 0,05. So that, there was a different significant between the biggest volume (500 liter), big (250-500), middle (100-249 liter) with dangue fever. The value of odds ratio (OR=4,417) it means that the family who have the biggest, bath tub middle and small will get 4,4 times dengue fever. Then the other who have a small bath tub.Conclusion:the smallest bath tub can be minimized of larvae and less the dengue fever risk. There was different significant between bath tub volume with Aedes Aegepthi Mosquito Larvae and dengue fever case. There advised to seek regular cleaning of bath tub, so it does’nt arise dirt/ moss which causes the impression of being a dark bath tub.